(untitled) (Environment & Health, 2017)
Background: During the last decades a process of the deterioration of the schoolchildren’s health state has been observed in Ukraine. For the period from 1986 to 2015 a number of schoolchildren with pathological disorders of all ages increased by 2.2 fold at primary school, by 2. 0 fold at middle, by 2.2 fold at senior. Therefore the issues of the schoolchildren’s health state control are extremely relevant today. Objective: We identified the preconditions of chronic diseases formation in the contemporary schoolchildren. Materials and methods: 382 schoolchildren of middle school age took part in the study, 274 schoolchildren with chronic somatic diseases and 108 without health problems were among them. Assessment of relative risks of some pathological changes in the children with chronic diseases was performed in comparison with the healthy ones. We used a multivariate regressive analysis for the determination of the dependence of the indices from operating factors. Results: The functional markers of the relative risk of chronic somatic diseases formation in the children and an insufficient level of physical readiness were identified. A method for the rough evaluation of the children’s health state only by functional indices of the organism and level of physical readiness was found, this allowed us to identify a group of "risk" of the emergence of pathological pathology.